It's time to re-evaluate the reporting of common measures from isokinetic dynamometers: isokinetic for torque, isotonic for power - Thompson, Brennan J. (Frontiers in Sports and Active Living, 2025)
Isokinetic dynamometry is commonly used to provide an objective and reliable assessment of muscle function across a variety of clinical, athletic and research settings. Important muscle function variables that are commonly assessed are torque- and power- related measures. Isokinetic mode is overwhelmingly used to provide these variables, and has been so for decades; however, this mode may not be the best suited to examine power variables. The article aims to explore this issue through conceptual evaluation and empirical results using unpublished data. The implication is that due to the almost complete lack of unique information that power provides additional to torque in isokinetic mode, the isotonic mode is better suited to assess power for functional, operational, and methodological reasons. Thus, muscle function tests on an isokinetic dynamometer provide more fitting and useful data when isokinetic mode is used to determine torque measures, and isotonic mode is used to provide power measures.